Influences of hand dominance on the maintenance of benefits after home-based modified constraint-induced movement therapy in individuals with stroke - Lima R.C.M. (2014)
© 2014, Revista Brasileira de Fisioterapia. All rights reserved.Objective: To investigate the influence of hand dominance on the maintenance of gains after home-based modified constraint-induced movement therapy (mCIMT). Method: A previous randomized controlled trial was conducted to examine the addition of trunk restraint to the mCIMT. Twenty-two chronic stroke survivors with mild to moderate motor impairments received individual home-based mCIMT with or without trunk restraints, five times per week, three hours daily over two weeks. In this study, the participants were separated into dominant group, which had their paretic upper limb as dominant before the stroke (n=8), and non-dominant group (n=14) for analyses. The ability to perform unimanual tasks was measured by the Wolf Motor Function Test (WMFT) and the Motor Activity Log (MAL), whereas the capacity to perform bimanual tasks was measured using the Bilateral Activity Assessment Scale (BAAS). Results: Analysis revealed significant positive effects on the MAL amount of use and quality of the movement scales, as well as on the BAAS scores after intervention, with no differences between groups. Both groups maintained the bimanual improvements during follow-ups (BAAS-seconds 0.1, 95% CI -10.0 to 10.0), however only the dominant group maintained the unilateral improvements (MAL-amount of use: 1.5, 95% CI 0.7 to 2.3; MAL-quality: 1.3, 95% CI 0.5 to 2.1). Conclusions: Upper limb dominance did not interfere with the acquisition of upper limb skills after mCIMT. However, the participants whose paretic upper limb was dominant demonstrated better abilities to maintain the unilateral gains. The bilateral improvements were maintained, regardless of upper limb dominance.